Diffusion of Cholesterol and Its Precursors in Lipid Membranes Studied by (1)H Pulsed Field Gradient Magic Angle Spinning NMR - Scheidt, Holger A. (Biophysical Society, 2005)
Cholesterol content is critical for membrane functional properties. We studied the influence of cholesterol and its precursors desmosterol and lanosterol on lateral diffusion of phospholipids and sterols by (1)H pulsed field gradients (PFG) magic angle spinning (MAS) NMR spectroscopy. The high resolution of resonances afforded by MAS NMR permitted simultaneous diffusion measurements on 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and sterols. The cholesterol diffusion mirrored the DPPC behavior, but rates were slightly higher at all cholesterol concentrations. DPPC and cholesterol diffusion rates decreased and became cholesterol concentration dependent with the onset of liquid-ordered phase formation. The activation energies of diffusion in the coexistence region of liquid-ordered/liquid-disordered phases are higher by about a factor of 2 compared to pure DPPC and to the pure liquid-ordered state formed at higher cholesterol concentrations. We assume that the higher activation energies are a reflection of lipid diffusion across domain boundaries. In lanosterol- and desmosterol-containing membranes, the DPPC and sterol diffusion coefficients are somewhat higher. Whereas the desmosterol rates are only slightly higher than those of DPPC, the lanosterol diffusion rates significantly exceed DPPC rates, indicating a weaker interaction between DPPC and lanosterol.